DAMPAK PERNIKAHAN DINI TERHADAP KEHARMONISAN KELUARGA - ibnu fauzan; ibnu fauzan (INKLUSIF (JURNAL PENGKAJIAN PENELITIAN SYARIAH DAN ILMU HUKUM), 2023)
This early marriage seems to be a "fad" that repeats. In the past, young marriage was considered commonplace. Years change, more and more are against marriage at an early age. This phenomenon is back again, if in the past parents wanted their children to marry young for various reasons, now many teenagers themselves dream of marrying young. They are not village teenagers, but teenagers in big cities. In addition, some teenagers view that marrying young is an option so that they avoid committing sinful acts, such as having sex before marriage. Marriage at a young age is only a piece of the social reality that society is currently facing. Among adolescents, marriage at a young age is seen as a way out to avoid free sex. There are also those who do it out of necessity and because they become pregnant out of wedlock. This opinion may be true, but marriage is certainly not just uniting oneself in a marriage as an answer to the problems of life that are being faced. Marriage is a provision of life that must be prepared carefully.This type of research is library research (library research), in the sense that all data sources come from written materials in the form of books, documents, magazines and texts that are related to the topic of discussion through a review of various literature related to research which includes primary, secondary data. , dantertier. The data collected, read.The results of this study are marriages at a young age that are carried out by someone who essentially lacks preparation or maturity both biology, psychologically and socio-economically. Young marriages have a real impact on the level of family welfare. This can be seen from the side of family harmony and peace, the harmony and harmony of young couples and the fulfillment of their material and spiritual needs is still not good.Â Keywords: Maqashid Syari'ah and Marriage Law.